2001
DOI: 10.34080/os.v11.22859
|View full text |Cite
|
Sign up to set email alerts
|

Migration patterns of Nordic Greylag Geese Anser anser

Abstract: Migration patterns of Nordic Greylag Geese Anser anser were studied by means of neck-collaring. A total of 4,173 birds (738 breeders, 1,999 goslings and 1,436 moulters; most moulters subsequently identified as belonging to a specified breeding population) was marked throughout Norway, Sweden, Denmark and Finland during 1984–1994. This report is based on observations made up to 30 June 1995. In general, Norwegian Greylag Geese left their breeding areas rapidly for staging areas in Denmark and/or the Netherlands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…2). Additionally, Finnish greylag geese have formerly been observed to winter as far south as in Spain (along WF) or in North Africa (along CF, Andersson et al, 2001). Our data therefore indicates that wintering sites have shifted northwards since that (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2). Additionally, Finnish greylag geese have formerly been observed to winter as far south as in Spain (along WF) or in North Africa (along CF, Andersson et al, 2001). Our data therefore indicates that wintering sites have shifted northwards since that (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Lesser White-fronted Geese that occurred in Greylag Goose flocks had most likely arrived together with them from the Netherlands (cf. Andersson et al 2001), while those, if any, that occurred in flocks of Tundra Bean Goose probably had arrived together with that species from Germany. Direct migration from the Pannonic area cannot be fully ruled out, however, notwithstanding that the Lesser White-fronted Goose migration in Hungary followed a narrow route east of the River Tisza (Sterbetz 1982).…”
Section: Migration Routesmentioning
confidence: 95%
“…Median dates were used to describe differences between sets of last-or firstsightings. Several studies have demonstrated that first-and last-sightings are good representatives of the true arrival and departure dates, respectively (e.g., Persson 1993, Andersson et al 2001.…”
Section: Methodsmentioning
confidence: 99%